1997
DOI: 10.1046/j.1423-0410.1997.7240233.x
|View full text |Cite
|
Sign up to set email alerts
|

Gel Test Application for IgG Subclass Detection in Auto‐Immune Haemolytic Anaemia

Abstract: The gel test is more sensitive than other procedures for the determination of IgG subclass and has the advantages of simplicity, rapidity, low cost, and stability of the agglutinates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The patient populations to consider include alloimmunized transfusion patients, pregnant women with a possibility of HDN, and patients with autoimmune hemolytic anemia (AIHA). Detailed studies in AIHA patients have demonstrated that a mixture of IgG subclasses is the most common presentation, and has a stronger association with hemolysis than isolated IgG subclasses 14,15 . In such patients, the monoclonal anti-IgG would still pick up the anti-RBC antibodies, as a mixture of IgG subclasses is present.…”
Section: Discussionmentioning
confidence: 99%
“…The patient populations to consider include alloimmunized transfusion patients, pregnant women with a possibility of HDN, and patients with autoimmune hemolytic anemia (AIHA). Detailed studies in AIHA patients have demonstrated that a mixture of IgG subclasses is the most common presentation, and has a stronger association with hemolysis than isolated IgG subclasses 14,15 . In such patients, the monoclonal anti-IgG would still pick up the anti-RBC antibodies, as a mixture of IgG subclasses is present.…”
Section: Discussionmentioning
confidence: 99%
“…However, several isotypes are found simultaneously in 59% of patients with IgG-positive DAT. 7 These IgG isotypes influence the pathogenicity and the efficiency of immune clearance through the binding of several Fcg receptors on effectors cells. 3,4 Thus, the presence of the FcgRIIa131H as single allele which bind with more IgG isotypes may explain the association between FcgRIIa-131HH genotype and AIHA in WM patients by increasing the clearance of IgG opsonized red cells.…”
mentioning
confidence: 99%
“…5,6 However, in those studies, only HUMARA assay was performed to assess clonality, a methylation-based test that is not completely reliable for patients' samples analysis because of possible abnormal DNA methylation in malignancies. 7 We studied a series of female ET patients in whom XCIPs had previously been analyzed by our group using both gene methylation and expression assays in all hematopoietic cell lineages 1,2 for the presence of mutant JAK2 and tested if the mutation correlated with monoclonal phenotype that would be expected if JAK2 mutation plays a role in disease development.…”
mentioning
confidence: 99%
“…Commercially available microtubes containing either gel or microbeads can be used for red blood cell grouping, antibody screening and identification, as well as for cross-matching [1, 2]. They have also appeared to be useful in patients with autoimmune hemolytic anemia mainly for the detection of autoantibody and IgG subclass determination in ‘Coombs-negative’ anemia [3, 4]. Moreover, the microcolumn technology has the advantage that it is rapid, its interpretation is easy, and the results can be stored.…”
Section: Introductionmentioning
confidence: 99%